Pengaruh Budaya Organisasi Dan Kinerja Guru Terhadap Mutu Proses Pembelajaran Madrasah Ibtidaiyah Negeri Bandar Lampung - Rohman, Asep (Letiges, 2021)
The purpose of study was to determine the influence of organizational culture on the learning process quality, the influence of teacher performance on the learning process quality and the influence of organizational culture and teacher performance on the learning process quality at Madrasah Ibtidaiyah Negeri in Bandar Lampung City. The research data is in the form of numbers which the answers to the respondents' questionnaires. Researchers conducted validity tests, reliability tests, normality tests as prerequisite tests for variable instrument items. The results showed that the simple linear regression of the organizational culture variable on the quality process was 9.560> 2.104 with an R square of 0.67 or 67% classified as moderate with a relationship of Y = 12.527 + 0.783X. Simple linear regression of organizational culture variable on quality process is 4.813>2.104 with R square of 0.34 or 34% classified as low with the relationship Y=23,663+0,577X. Multiple linear regression of organizational culture and teacher performance variables on the quality process of 59.220>3.20 with an R square of 0.729 or 72.9% classified as high with the relationship Y=3,900+0.667X1+0.269X2, meaning that a 1% change in the value of the Y variable affects the variable X1 is 0.667 and X2 is 0.269.